Optimizing site-based conservation approach to secure key species in Wallacea hotspot, Indonesia - Udin Jihad. S.; Teguh Prawira Wahyu; Widyanto Adi; Ismar Widyasari Vincentia (BIO Web of Conferences)
Wallacea is a globally important biodiversity area, home to many endemic and endangered species. However, habitat loss, poaching, and unsustainable resource use continue to threaten these species, necessitating innovative conservation strategies. This paper examines the optimization of a site-based conservation approach as an effective strategy to protect key species in Wallacea. Site-based conservation focuses on protecting critical habitats and ecosystems that support species survival while addressing local threats. By combining scientific research, community engagement, and enforcement of conservation regulations, this approach aims to create a sustainable balance between human activities and biodiversity conservation. Key elements of this optimized strategy include habitat restoration, strengthening protected areas, and the use of community-based monitoring systems. The involvement of local communities ensures long-term conservation outcomes by aligning their interests with conservation goals. In addition, the use of species encounter monitoring tools can provide accurate data for adaptive management. Case studies from the Program Kemitraan Wallacea 2 (PKW 2) demonstrate the success of this approach, highlighting how targeted, site-based efforts can stabilize populations of globally threatened species such as Banggai Cardinalfish, Dugong, Turtles, and several shark species. The paper concludes with recommendations for relevant site-level protection schemes to be replicated to preserve biodiversity.